Remote sensing estimations of water quality dynamics in the Asian mega deltas - Jampani, Mahesh (United Nations Office for Outer Space Affairs (UNOOSA), 2024)
In the Asian Mega Deltas, Mekong, Irrawaddy, and Ganges, millions of people depend on the aquatic environments for livelihoods. Inhabitants in these delta systems often face health risks that are amplified by anthropogenic pollution loads from terrestrial environments and tidal incursions from coastal environments. The water quality deterioration in these delta systems is complex, often due to a lack of wastewater treatment capacities, upstream activities, climate change implications, and inefficient water management practices. These impacts often lead to the contamination of both riverine and coastal ecosystems, adversely affecting local livelihoods and economies. Therefore, there is an urgent need to understand water quality dynamics within these deltas. The current research leverages multi-sensor satellite imagery in combination with predictive 20modelling to address these challenges. Overall, this research aims to evaluate the spatial and temporal variations of water quality and provide an essential understanding of contaminant plume extent, seasonal dynamics, and pollution occurrence based on events. This research and analysis provide insights into pollution dynamics, evaluating impacts, and developing robust strategies to improve water management in delta systems, thereby mitigating public health risks.